2016
DOI: 10.1111/cyt.12368
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemistry for Claudin‐18 and Maspin in biliary brushing cytology increases the accuracy of diagnosing pancreatobiliary malignancies

Abstract: Immunocytochemical staining for Claudin-18 and Maspin improved the diagnostic sensitivity for pancreatobiliary adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Immunocytochemical studies using Mapsin and Claudin-18 are also reported to be helpful in improving the sensitivity of bile duct brushings. 19 Measurement of DNA methylation status of HOXA1 and NEUROG1 genes in left over brushed biliary cells is reported to increase sensitivity of biliary brush material. 20 Along with technical improvements in navigation of the bile ducts, we can expect a continuing evolution of sample types and tests aimed at improving the diagnostic performance of specimens from the biliary tree.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical studies using Mapsin and Claudin-18 are also reported to be helpful in improving the sensitivity of bile duct brushings. 19 Measurement of DNA methylation status of HOXA1 and NEUROG1 genes in left over brushed biliary cells is reported to increase sensitivity of biliary brush material. 20 Along with technical improvements in navigation of the bile ducts, we can expect a continuing evolution of sample types and tests aimed at improving the diagnostic performance of specimens from the biliary tree.…”
Section: Discussionmentioning
confidence: 99%
“…First, the authors eliminated all cases that had scant cellularity. Other studies have also tried to improve the accuracy of biliary cytology by improving specimen quality . It would be interesting to know what the performance of these new criteria would be on all cases, not just highly cellular ones.…”
mentioning
confidence: 99%
“…Other studies have also tried to improve the accuracy of biliary cytology by improving specimen quality. [6][7][8][9][10] It would be interesting to know what the performance of these new criteria would be on all cases, not just highly cellular ones. Second, the images that the authors illustrate are beautiful.…”
mentioning
confidence: 99%
“…Maspin.-Maspin is a tumor suppressor that is overexpressed in more than 90% of pancreatic ductal adenocarcinomas, 1 62, 16 7, 18 3,1 84 59% to 100% of gallbladder adenocarcinomas, 168,185 57% to 91% of adenocarcinomas of extrahepatic bile ducts, 186,187 and more than 70% of intrahepatic cholangiocarcinomas. 167,188 Malignant cells typically show strong and diffuse nuclear and cytoplasmic Figure 11.…”
mentioning
confidence: 99%
“…Benign pancreatic ducts are usually negative for maspin expression, but benign epithelial cells lining the gallbladder and extrahepatic bile ducts have been shown to be positive at a high frequency. 186,187,189 The staining can thus be difficult to interpret despite the observations that positive staining in benign biliary epithelial cells is usually focal/patchy and weaker in intensity in comparison with that seen in malignant cells.…”
mentioning
confidence: 99%